2018
DOI: 10.1111/cen.13723
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadism and male obesity: Focus on unresolved questions

Abstract: Obesity, increasing in prevalence globally, is the clinical condition most strongly associated with lowered testosterone concentrations in men and presents as one of the strongest predictors of receiving testosterone treatment. While low circulating total testosterone concentrations in modest obesity primarily reflect reduced concentrations of sex hormone binding globulin, more marked obesity can lead to genuine hypothalamic-pituitary-testicular axis (HPT) suppression. HPT axis suppression is likely mediated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(135 citation statements)
references
References 126 publications
(198 reference statements)
2
122
1
10
Order By: Relevance
“…Dhindsa et al reported that total and free estradiol in hypogonadal diabetic men are even lower than in eugonadal diabetic men. This result led some authors to hypothesize that as circulating testosterone is the main substrate for aromatase, low testosterone concentration should be reflected in low estradiol concentration in hypogonadal men . In fact, a recent study by Ghanim et al reported that hypogonadal diabetic men's adipocytes expressed less aromatase and oestrogen receptor alpha when compared with eugonadal diabetic men.…”
Section: Obesity Prompts Hpt Axis Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dhindsa et al reported that total and free estradiol in hypogonadal diabetic men are even lower than in eugonadal diabetic men. This result led some authors to hypothesize that as circulating testosterone is the main substrate for aromatase, low testosterone concentration should be reflected in low estradiol concentration in hypogonadal men . In fact, a recent study by Ghanim et al reported that hypogonadal diabetic men's adipocytes expressed less aromatase and oestrogen receptor alpha when compared with eugonadal diabetic men.…”
Section: Obesity Prompts Hpt Axis Dysfunctionmentioning
confidence: 99%
“…Male hypogonadism is defined as a syndrome characterized by androgen deficiency, which can be classified as primary or secondary according to the aetiology of testosterone deficiency. Primary hypogonadism is caused by a testicular inability to secrete testosterone in normal amounts in order to sustain the physiological circulating concentrations, while secondary hypogonadism is due to reduced or inappropriately normal gonadotropin release and consequent disruption of the hypothalamic‐pituitary‐testicular (HPT) axis normal functioning . In brief, the HPT axis is regulated by kisspeptins, a family of peptides coexpressed in the hypothalamus, which are responsible to regulate the secretion and release of hypothalamic gonadotropin‐releasing hormone (GnRH).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In middle-aged and older men, obesity is consistently associated with lower circulating testosterone without elevation of LH and FSH, 18,19 and loss of excess weight in obese men is associated with recovery of endogenous testosterone production. [20][21][22] In men with class 1 and 2 obesity, this may be attributable to lower SHBG and hence lower testosterone concentrations.…”
Section: Obesitymentioning
confidence: 99%
“…2 Managing the obesity, may also have additional health benefits. 18 Obesity is a risk factor for insulin resistance and for type 2 diabetes, and men with lower testosterone concentrations are more likely to have or to develop metabolic syndrome or diabetes. Short-term studies have shown that testosterone treatment in carefully selected obese men may have modest benefits on symptoms of androgen deficiency and body composition even additive to diet alone.…”
Section: Obesitymentioning
confidence: 99%